Chemosensitization of doxorubicin in multidrug-resistant cells by unimolecular micelles via increased cellular accumulation and apoptosis. (19th February 2016) - Wang, Meng; Han, Min; Li, Ying; Jin, Yi; Gao, Jian-Qing
Abstract: Objectives: Unimolecular micelles were prepared by modification of polyamidoamine (PAMAM) dendrimers using Pluronic F127 (PF127), which is expected to reverse multidrug resistance (MDR). And the reversal mechanisms have been studied. Methods: Characterization of the products was carried on. MTT assay was used to evaluate the cytotoxicity of the DOX-loaded conjugates. Cellular uptake study was measured by confocal laser scanning microscope and flow cytometry. Apoptosis assay was identified by Annexin V-FITC/PI apoptosis assay and Hoechst 33 342 staining. Key findings: Improved cytotoxicity of DOX-loaded conjugates in MCF-7/ADR cells (as much as 33-fold according to the IC50 values) was observed in contrast with that of free DOX. The DOX-loaded conjugates induced a much quicker and 100% uptake in MCF-7/ADR cells, and more than fivefold accumulation of DOX-loaded conjugates was observed compared with free DOX. Apoptosis assay showed that DOX-loaded conjugates decreased the cell viability from 81.87 ± 5.94% to 54.83 ± 3.63% (DOX concentration 2 μg/ml). At 48 h, more accumulation and distribution in the nuclei were observed after treatment with DOX-loaded conjugates. Conclusions: PF127-PAMAM conjugates showed superiority in the treatment of MCF-7/ADR, which implied the potential vehicles of anticancer drugs for the reversal of MDR.